Dynamic Distributional Effects of Fiscal Consolidation: A Sample of 16 OECD Countries - Okeke, Angela; Alexiou, Constantinos; Nellis, Joseph (Panoeconomicus, 2025)
We explore the long-term distributional consequences of fiscal adjustment episodes and the dynamic consequences of fiscal consolidation for countries with large sized consolidations vis-a-vis countries with small sized consolidations. In this direction, panel ARDL and impulse response functions using local projections are adopted for a panel of 16 OECD countries covering the period 1980 to 2019 based on a newly updated fiscal adjustment dataset, compiled by Gustavo Adler et al. (2024). The evidence suggests that adverse income disparities which tend to arise upon implementation of fiscal adjustments are dynamic and persist through the long run. While baseline results for the Gini suggest that long-term inequality levels hold at approximately the same as peak levels (by the 7th period), inequality measured by the bottom 40 income share appear to exhibit peak levels at the 14th period, suggesting a more persistent impact. Disaggregating impact by adjustment size, evidence is also offered for small-sized adjustment and large-sized adjustment countries showing that small-sized adjustments lead to gradual but prolonged inequality effects, while large-sized adjustments generate steeper but shorter-lived inequality increases. JEL: E62; H2; H5; H6